2014
DOI: 10.1055/s-0034-1370957
|View full text |Cite
|
Sign up to set email alerts
|

Amputation der Hand bei nekrotisierender Fasziitis: Ein Fallbericht

Abstract: We report the case of an 81-year-old woman who fell at home on her left hand and suffered a laceration of her forehead. Within days a fulminant necrotizing fasciitis of the hand from group A β-haemolytic streptococcus developed. Lacking an apparent local germ entry point at the hand, the infection was initially misinterpreted as compartment syndrome. The patient's life was saved by amputation of the hand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
(6 reference statements)
0
3
0
1
Order By: Relevance
“…Within days a fulminant, streptococcal necrotizing fasciitis of the hand developed. The patient's life was saved by amputation of the hand [5]. Other authors reported about two patients with necrotising fasciitis of the hand, whose lives were saved thanks to intensive medical therapy, as well as by radical, serial surgical debridement [6].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Within days a fulminant, streptococcal necrotizing fasciitis of the hand developed. The patient's life was saved by amputation of the hand [5]. Other authors reported about two patients with necrotising fasciitis of the hand, whose lives were saved thanks to intensive medical therapy, as well as by radical, serial surgical debridement [6].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The trauma history may provide a hint to possible causative microorganisms (Table 1). A gout tophus that is infected and perforates into the joint [26], or adjacent severe skin and softtissue infection [27,28], are less frequently reported routes of exogenous infections.…”
Section: Septic Arthritismentioning
confidence: 99%
“…In a study that included 418 hand infections, 71.3% of patients had a body temperature of <37 C and 63% had normal Creactive protein levels at admission [6]. Conversely, the presence of markedly elevated laboratory parameters indicates a remote source of infection [30,39], a severe and rapidly spreading soft-tissue infection [27,28], or concomitant crystalline inflammation [46].…”
Section: Laboratory Findingsmentioning
confidence: 99%
“…Musculoskeletal diseases · Debridement · Antibiotics · Intensive care unit · Soft tissue injuries stamm sicher verhindert und das Über-leben des Patienten gewährleistet werden kann [12]. Hier gilt dann klar das Konzept "life before limb".…”
Section: Introductionunclassified